From governability to ungovernability: Race, class and authority in South Africa's black cities - Bozzoli, Belinda (My University, 1996)
Soweto, Alexandra and Sharpeville were symbols with great resonance in the global arena of anti-apartheid struggles. Tembisa, Katlehong, Atteridgeville, Wattville - there are too many to mention - all have had considerable local and national significance. These locations, townships, ghettoes, are the places to which black people were consigned during the years of segregation and apartheid; within which the flames of resistance were ignited during the struggles of the post-1976 era, where homes and jobs are scarce and lawlessness is rife; and where, today, new local authorities are attempting to achieve legitimacy and to exact rent and service payments from an unwilling populace. Much has been written about the better known amongst these townships. There are vivid portrayals of moments of crisis and resistance; there are detailed studies of social cleavage and cultural interplay, and there are analytical pieces. In addition there are studies of different aspects of social and cultural life in townships - whether these be focussed upon gangs, liquor brewing, music, sport or other leisure activities. This paper seeks, whether boldly or foolishly, to draw together some of the themes covered in these diverse pieces, and to add new ones - the latter drawn to some extent from a case study of resistance in Alexandra township in the 1980s. !t addresses itself to the question: how do we best understand the township rebellions of the nineteen eighties and their aftermath?
African Studies Seminar series. Paper presented 18th March, 1996
Keywords: Cities and towns. South Africa. Gauteng; Blacks. South Africa. Gauteng. Economic conditions; Local government. South Africa. Gauteng; Blacks. South Africa. Gauteng. Social conditions